All-Optical Switch Based on Thermo-Optic Effect in Graphene-on- Si3N4 Structure - Hamodi, Hayder Maki; Fyath, Raad Sami (Al-Nahrain Journal for Engineering Sciences, 2024)
A high-performance Mach-Zehnder interferometer (MZI) based all-optical switch using graphene on silicon nitride (Si3N4) is proposed and simulated. Graphene absorbs pump power (λ = 980 nm) on Si3N4 waveguide, generating heat. The heat affects the Si3N4 waveguide, causing a change in its refractive index due to thermo-optic effect. By tuning the probe phase (λ = 1550 nm) in the Si3N4 arm with graphene on top, all optical switching can then be carried out. An extinction ratio ranges of 13-25 dB and pump power range 20-270 mW. These findings demonstrate that our suggested configuration offers a useful integrated part for the creation of effective all-optical control devices on the insulator platform with a quick switching rate. Moreover, the suggested design might be able to achieve a wide bandwidth by utilizing an integrated MZI structure.